Combined evaluation of right ventricular function using echocardiography in non‐ischaemic dilated cardiomyopathy. (4th August 2021) - Ishiwata, Jumpei; Daimon, Masao; Nakanishi, Koki; Sugimoto, Tadafumi; Kawata, Takayuki; Shinozaki, Tomohiro; Nakao, Tomoko; Hirokawa, Megumi; Sawada, Naoko; Yoshida, Yuriko; Amiya, Eisuke; Hatano, Masaru; et al.
Abstract: Aims: Although comprehensive assessment of right ventricular (RV) function using multiple echocardiographic parameters is recommended for management of patients with non‐ischaemic dilated cardiomyopathy (DCM), it is unclear which RV parameters to combine. Additionally, normalization of RV parameters by estimated pulmonary artery systolic pressure (PASP), in consideration of RV–pulmonary artery coupling, may be clinically significant. The aim of our study was to elucidate the best combination of echocardiographic RV functional parameters, with or without indexing for PASP, to predict outcome in patients with heart failure with reduced ejection fraction secondary to DCM. Methods and results: We retrospectively analysed 109 DCM patients with left ventricular ejection fraction <40%. RV size was assessed by RV end‐diastolic area (RVEDA) and RV end‐systolic area (RVESA) from RV‐focused apical four‐chamber view. RV function was assessed by fractional area change (FAC) and tricuspid annular plane systolic excursion (TAPSE) and by RV longitudinal strain (RVLS) using two‐dimensional speckle‐tracking echocardiography. All functional parameters were also indexed for estimated PASP. Cox analyses were used to evaluate the association of RV morphology and functional parameters with 1 year outcome (composite of left ventricular assist device implantation and all‐cause death). Area under the curve was used to compare prognostic values. Mean age was 44 ± 14 years, and 76 (69.7%) were men. Mean left ventricular ejection fraction was 21.9%, median RVEDA was 22.1 cm 2, FAC was 27.0%, TAPSE was 15.0 mm, and RVLS was −12.5%. Forty‐one (37.6%) patients experienced the primary outcome. Multivariate Cox analysis revealed that RVEDA, RVESA, FAC, TAPSE, RVLS, FAC/PASP, and RVLS/PASP were independent predictors for primary outcome (all P  < 0.05). However, normalization with PASP did not improve area under the curve for any RV functional parameters. When we evaluate hazard ratios according to the combination of two echocardiographic parameters of RV function, patients with impairment of both FAC (<27%) and RVLS (>−8.6%) had significantly higher hazard ratio than those with either impairment alone (11.3 vs. 3.4, P  < 0.001); the other combinations did not improve prognostic value. Conclusions: Normalizing echocardiographic RV parameters for PASP did not improve the prognostic values for our population. Meanwhile, combined evaluation of FAC and RVLS improved risk stratification in patients with heart failure with reduced ejection fraction secondary to DCM.